The global prevalence of complete hearing loss in 204 countries and territories from 1992 to 2021: a systematic analysis for the global burden of disease study 2021 - Huang, Guan-Jiang; Fan, Zhi-Jun; Lu, Biao-Qing (Frontiers in Public Health, 2025)
BackgroundComplete hearing loss, especially the age-related type, poses a significant public health challenge globally. This study aims to assess the global burden on the prevalence of complete hearing loss from 1992 to 2021 and forecast trends up to 2036.MethodsUsing data from the Global Burden of Disease (GBD) Study 2021, we assessed the global burden of complete hearing loss across 204 countries and territories. We analyzed temporal trends in ASPR using Joinpoint regression, evaluated the contributions of age, period, and cohort effects through Age-Period-Cohort modeling, and performed decomposition analysis to determine the impact of demographic and epidemiological changes on prevalence trends. Predictions of future ASPR trends were made using Bayesian Age-Period-Cohort (BAPC) and Autoregressive Integrated Moving Average (ARIMA) models.ResultsBy 2021, the global prevalence of complete hearing loss had reached 9.9 million cases, with the ASPR declining from 134.35 to 117.79 per 100,000. The overall Estimated Annual Percentage Change (EAPC) was−0.45. The most significant reductions were observed in low-SDI regions, particularly Sub-Saharan Africa (EAPC: −0.74). In contrast, high-SDI regions, including North America and Western Europe, showed more modest declines (EAPC: −0.18). Notably, East Asia exhibited a 62.3% increase in prevalence, with high-income Asia Pacific showing the highest relative rise at 83.97%. Age-related hearing loss remained the dominant cause, especially among individuals aged 60 and above. Males were more affected than females. Population aging and growth were the major drivers of the increased prevalence in high-SDI regions, while population growth was the primary factor in low-SDI areas.ConclusionThe burden of complete hearing loss remains high in prevalence, particularly in aging populations within high-SDI regions, despite overall reductions in ASPR. Significant regional disparities remain, highlighting the need for targeted interventions to improve access to hearing care and affordable technologies in low-SDI regions.